A new species of Sangeeta Viraktamath from China (Hemiptera: Cicadellidae: Megophthalminae) - Zhang, Bin (Zootaxa, 2014)
The Oriental leafhopper genus Sangeeta, which belongs to the tribe Agalliini, was erected by Viraktamath (2011) with eight new species from Southeast Asia, of which two are from Vietnam, two from Indonesia, three from Malaysia and one from Laos. Members of the genus can be recognized by the following combination of characters: vertex distinctly short medially in dorsal view, face long and narrow with fine transverse dorsal striations, ocelli closer to each other than to adjacent eyes or as close to each other as to adjacent eye, subgenital plates with large and stout setae on ventral surface, dorsal apodeme of aedeagus well developed, aedeagal shaft apically flattened, hoodlike, with or without laterally laminated processes, gonopore subapical.